2018
DOI: 10.1021/acs.chemrestox.7b00303
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-SMILES-Based Nano-Quantitative Structure–Activity Relationship Model to Predict the Cytotoxicity of Multiwalled Carbon Nanotubes to Human Lung Cells

Abstract: Quantitative structure-activity relationship (QSAR) models for nanomaterials (nano-QSAR) were developed to predict the cytotoxicity of 20 different types of multiwalled carbon nanotubes (MWCNTs) to human lung cells by using quasi-SMILES. The optimal descriptors, recorded as quasi-SMILES, were encoded to represent the physicochemical properties and experimental conditions for the MWCNTs from 276 data records collected from previously published studies. The quasi-SMILES used to build the optimal descriptors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Six studies, out of the 86 gathered, used Genetic Algorithm (GA) for feature selection [30][31][32][33][34][35]. Five of them used Pearson correlation coefficients between pairs of variables to identify those that correlate with the endpoint or correlations among variables to avoid inter-correlations [36][37][38][39]. Few of the studies applied more than one feature selection technique.…”
Section: Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies, out of the 86 gathered, used Genetic Algorithm (GA) for feature selection [30][31][32][33][34][35]. Five of them used Pearson correlation coefficients between pairs of variables to identify those that correlate with the endpoint or correlations among variables to avoid inter-correlations [36][37][38][39]. Few of the studies applied more than one feature selection technique.…”
Section: Feature Selectionmentioning
confidence: 99%
“…This makes the development of classic QSAR difficult [82]. Toropova et al [83] suggested a quasi-SMILES approach to represent molecular structures, p-chem properties, and experimental conditions (eclectic data) with NMs [37,82]. The eclectic data are translated into optimal nano-descriptors (the sum of weights of quasi-SMILES) for the outcome prediction and Monte Carlo optimization is used to select the optimal descriptors.…”
Section: Molecular Structures' Codificationmentioning
confidence: 99%
“…Statistical parameters of the models were satisfactory [78]. Nano-QSAR models were constructed to predict the toxicity of 20 MWCNTs types (276 data records) towards human lung cells by using a quasi-SMILES optimal descriptor [80]. Quasi-SMILES were used to represent the physico-chemical properties and experimental conditions for the MWCNTs: Diameter, length, surface area, in vitro toxicity assay, cell line, exposure time, and dose.…”
Section: Multi-walled Carbon Nanotubes (Mwcnts)mentioning
confidence: 99%
“…Since its discovery, QSAR model has been widely applied to drug design as well as the prediction of their toxicity . Later, many studies demonstrated that the general QSAR paradigm could be further extended to nanomaterials and develop “nano‐QSAR” model which can establish predictive relationship between their physicochemical properties and biological effects (both desired and undesired) . This success largely depends on the application of high‐throughput techniques coupled with cluster analysis and data mining, by which a large number of biological data could be achieved and then integrated into the large‐scale modeling.…”
Section: Introductionmentioning
confidence: 99%